NeurimmiRs and Postoperative Delirium in Elderly Patients Undergoing Total Hip/Knee Replacement: A Pilot Study - Dong, Rui; Sun, Lingling; Lu, Yayuan; Yang, Xi; Peng, Mian; Zhang, Zongze (Frontiers in Aging Neuroscience, 2017)
Objective: Postoperative delirium is a frequent complication after surgery and its occurrence is associated with poor outcomes. The pathophysiology of this complication is not clear, but identification of risk factors is important for positive postoperative outcomes. The purpose of this study was to investigate the associations between the preoperative expression levels of microRNA (miR)-146a, miR-125b, and miR-181c in cerebrospinal fluid (CSF) and serum and the development and severity of postoperative delirium (POD) Methods: Forty elderly patients aged 65 years old and older admitted for elective total hip/knee replacement under spinal anesthesia. Preoperatively, baseline cognitive function was assessed using the Mini-Mental State Examination (MMSE). Each patient was interviewed daily on the first and second postoperative days. Delirium was diagnosed using the Confusion Assessment Method (CAM), and delirium severity was measured using the Memorial Delirium Assessment Scale (MDAS). Preoperative serum and CSF miRNA levels were determined by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Clinical trial registration: this study was registered at ClinicalTrials.gov (NCT02817386). Results: POD was detected in 27.5% (11/40) of patients. Up-regulation of miR-146a and miR-181c in CSF and down-regulation of miR-146a in serum were observed preoperatively in patients who developed POD, while patients with and without POD did not differ in serum or CSF levels of miR-125b. Delirious patients had higher CSF/serum ratios of miR-146a and miR-181c levels than non-delirious patients. The lower CSF miR-146a and CSF/serum miR-146a ratios were significantly associated with milder POD severity, represented by a lower MDAS score. Conclusion: The dysregulation of preoperative miR-146a and miR-181c in CSF and serum was associated with the development and severity of POD. These NeurimmiRs might participate in the neuropathogenesis of POD, pending further investigations.